Antidepressant-like effect of a new selenium-containing compound is accompanied by a reduction of neuroinflammation and oxidative stress in lipopolysaccharide-challenged mice. (September 2017) - Casaril, Angela M; Domingues, Micaela; Fronza, Mariana; Vieira, Beatriz; Begnini, Karine; Lenardão, Eder J; Seixas, Fabiana K; Collares, Tiago; Nogueira, Cristina W; Savegnago, Lucielli
Organoselenium compounds and indoles have gained attention due to their wide range of pharmacological properties. Depression is a recurrent and disabling psychiatric illness and current evidences support that oxidative stress and neuroinflammation are mechanisms underlying the pathophysiology of this psychiatric condition. Here, we evaluated the effect of 3-((4-chlorophenyl)selanyl)-1-methyl-1H-indole (CMI) in lipopolysaccharide (LPS)-induced depressive-like behaviour, neuroinflammation and oxidative stress in male mice. CMI pre-treatment (20 and 50 mg/kg, intragastrically) significantly attenuated LPS (0.83 mg/kg, intraperitoneally)-induced depressive-like behaviour in mice by reducing the immobility time in the tail suspension test (TST) and forced swimming test (FST). CMI pre-treatment ameliorated LPS-induced neuroinflammation by reducing the levels of interleukin (IL)-1β, IL-4 and IL-6 in the hippocampus and prefrontal cortex, as well as markers of oxidative damage. Additionally, we investigated the toxicological effects of CMI (200 mg/kg, i.g.) in the liver, kidney and brain through determination of the activity of aspartate aminotransferase (AST), alanine aminotransferase (ALT), δ-aminolevulinate dehydratase (δ-ALA-D) and creatinine levels. These biomarkers were not modified, indicating the possible absence of neuro-, hepato- and nephrotoxic effects. Our results suggest that CMI could be a therapeutic approach for the treatment of depression and other neuropsychiatric disorders associated with inflammation and oxidative stress.